2012
DOI: 10.1002/art.34651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of autoantibody specificities between traditional and bead‐based assays in a large, diverse collection of patients with systemic lupus erythematosus and family members

Abstract: Objective The replacement of standard immunofluorescence anti-nuclear antibody (ANA) methods with bead-based assays is a new clinical option. A large, multi-racial cohort of SLE patients, blood relatives and unaffected control individuals was evaluated for familial aggregation and subset clustering of autoantibodies by high-throughput serum screening technology and traditional methods. Methods Serum samples (1,540 SLE patients, 1,127 unaffected relatives, and 906 healthy, population-based controls) were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 74 publications
7
71
1
Order By: Relevance
“…A previous study conducted in Taiwan indicated that the positivity rate of ANA in patients with SLE was over 90% [17]. According to the study by Wichainun et al [18], the ANA test has a sensitivity of over 90% to detect SLE, which is considerably higher than those from other autoantibodies such as anti-dsDNA and anti-SSA/SSB [19]. Therefore, ANA test is a test of choice for initial screening of SLE among patients with multisystemic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted in Taiwan indicated that the positivity rate of ANA in patients with SLE was over 90% [17]. According to the study by Wichainun et al [18], the ANA test has a sensitivity of over 90% to detect SLE, which is considerably higher than those from other autoantibodies such as anti-dsDNA and anti-SSA/SSB [19]. Therefore, ANA test is a test of choice for initial screening of SLE among patients with multisystemic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibodies to dsDNA, chromatin, Ro/Sjögren's-syndrome-related antigen A (SSA), La/SSB, Sm, SmRNP complex and ribonucleoprotein (RNP) were detected using the xMAP BioPlex 2200 multiplex system (Bio-Rad Technologies, Hercules, California, USA) 16. WISH Reporter cells (CAT# CCL125; ATCC) were used to measure the ability of sera to induce type I IFN-related gene transcription 6.…”
Section: Methodsmentioning
confidence: 99%
“…7 Autoantibody specificities were compared using a multiplexed, bead-based assay (BioPlex 2200, Bio-Rad, Hercules, California, USA) that simultaneously detects dsDNA, chromatin, ribosomal P, Ro/SSA (60 and 52 kDa), La/SSB, Sm, SmRNP complex, RNP, centromere B, Scl-70 and Jo-1 autoantibodies. 8 Anti-dsDNA is reported in IU/mL with a manufacturer-specified positive cut-off of 10.0 IU/mL, and other specificities as an Antibody Index (AI) value (range 0-8) based on the fluorescence intensity of each of the other autoantibody specificities, with a manufacturer-recommended positive cut-off of AI=1.0. 8…”
Section: Autoantibody Detectionmentioning
confidence: 99%